The role of English for specific purposes (ESP) in supporting the linguistic dimension in English-medium instruction (EMI) - Francesca Costa; Lynn Mastellotto (Universitat Autònoma de Barcelona, 2022)
Partly because of the Bologna Declaration, the so-called English-Medium Instruction (EMI) courses in universities have undergone a strong surge in the last 15 years. This initial phase of growth in EMI has had an impact on LSP (Language for Specific Purposes) courses, which have in some cases suffered a consequent decline. This article seeks to highlight the potential of LSP to prepare students in EMI communication, support academic disciplinary skills, develop transversal skills, and foster intercultural communication. The study analyses an LSP-focused curricular design that aims to help students develop English-language communicative effectiveness for a domain-specific context: social and human services. The various integrative practices inherent in LSP instruction call attention to its potential as a harmonizing and empowering force for content- and language-integrated learning when used alongside EMI. Keywords: English-Medium Instruction (EMI); Language for Specific Purposes (LSP); English for Specific Purposes (ESP); Content-and-language integrated learning (CLIL); Integrating content and language in higher education (ICLHE).